AYURVEDIC TREATMENT OF ALLERGIC RHINITIS - A CASE STUDY - Ankit, Sharma; R. K., Soni (International Journal of Ayurveda and Pharma Research, 2017)
Respiratory allergies are major cause of morbidity in both children and adult. Allergic rhinitis is one of the prime disease of respiratory system found in all age groups irrespective of sex. Among Nasagat rogas Pratishyaya is the one which is described by almost all the Acharyas in detail, which shows its importance due to dreadful nature. This disease is also known for its recurrence and chronicity if not treated from its root. Sedentary Life style like having exposure to cold weather, Air Conditioner and cooler, and food habits like consuming junk foods, ice creams cold drinks, curd, sour items like pickles, sauce etc. are the major causative factors of this disease. The disorder creates headache and fatigue, limits routine activities, interferes with sleep and results in poor work performance. Its clinical features like Tanu nasa srava, Shirahshula, Kshvathu etc. are very much similar to Vataja pratishyaya features described in Ayurved. Modern medicine undoubtedly relieves symptoms very fast but permanent cure is very much possible through holistic approach of Ayurvedic science. Ayurved, the science of life if applied systematically has the ability to ensure complete cure. Panchkarma is a potent tool of Ayurved to cure the disease from its root. Nasya karma is an important part of Panchkarma and is the best treatment for Urdhavjatruroga. A chronic case of Allergic Rhinitis is presented in this paper which got cured by adopting systematic Ayurvedic approach of Vataj pratishyaya line of treatment by using Vyaghri haritaki and Anu taila nasya.